If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(7*x)/2-(3/2)-(4/1) = 5*x+1/3 // - 5*x+1/3
(7*x)/2-(5*x)-(3/2)-(4/1)-(1/3) = 0
(7*x)/2-5*x-3/2-1/3-4 = 0
-3/2*x-35/6 = 0 // + 35/6
-3/2*x = 35/6 // : -3/2
x = 35/6/(-3/2)
x = -35/9
x = -35/9
| (a-5)(a-5)=196 | | 1045.95-1045.95x/100=617.05 | | 0=25x^2-70x+13 | | x-3.9=4.1 | | 25x^2-70x+13=0 | | x^4-1.36x^2+1=0.909 | | 1045.95-x/100=617.05 | | 25x^2-70+13=0 | | 2l-18=36 | | 2n+1=56 | | 8x+y=198 | | (2x-7)(x^2-9)(2x-5)-91=0 | | 5x+8y=198 | | 20x/100=516.06 | | 8x+5y=198 | | 20x/100=6888.52 | | 1/4x120 | | 4+2/u-3u/u+5 | | 6/x+4*x=11 | | 3628800=20*80 | | 6/x+4x=11 | | 8-1234=x | | x/y/z=30 | | 5abcd=8 | | 2=8*2x | | 3628800=x+8(7-x(2x+8)-7x)+12 | | 20x/100=0.04 | | 3a=5b | | 20x/100=119.59 | | 1=-1*(-1) | | 3+x*(x-5*(2x+8)-8x)+23=x-32*(34+x*(5x-12)+12x)-65 | | 2k-3(k-4)=-3 |